2009
DOI: 10.1080/00223890902794275
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Assessment With Children: A Pilot Study of Treatment Acceptability and Outcome

Abstract: Therapeutic Assessment (TA) with children is a hybrid of psychological assessment and short-term intervention. It uses the ongoing process and results of psychological assessment to enhance parents' understanding of their child and to facilitate change. Clinical reports and single case studies suggest that TA with children is an acceptable and effective brief intervention. However, no aggregate data have been published to support this claim. This pilot study investigated the acceptability and preoutcome-postou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 23 publications
5
44
0
Order By: Relevance
“…Tharinger, Finn, Gentry, Hamilton, Fowler, Matson, Krumholz, and Walkowiak (2009) found TA with children to be associated with significantly decreased child symptomatology and improved family functioning.…”
Section: Empirical Research On Collaborative and Therapeutic Assessmementioning
confidence: 97%
See 2 more Smart Citations
“…Tharinger, Finn, Gentry, Hamilton, Fowler, Matson, Krumholz, and Walkowiak (2009) found TA with children to be associated with significantly decreased child symptomatology and improved family functioning.…”
Section: Empirical Research On Collaborative and Therapeutic Assessmementioning
confidence: 97%
“…To date, all of the empirical research on collaborative and Therapeutic Assessment has focused on individual (Ackerman et al, 2000;Finn & Tonsager, 1992;Hilsenroth et al, 2004;Newman & Greenway, 1997) and family clients (Smith et al, 2009;Tharinger et al, 2009;Tharinger, Finn, Wilkinson, & Schaber, 2007). However, an accumulating body of case material suggests collaborative and Therapeutic Assessment techniques may also be useful for psychologists working with couples, either as a precursor or supplement to traditional couples therapy (Butcher, 1990;Dorr, 1981;Finn, 2007;Richman & Davidoff, 1971).…”
Section: Empirical Research On Collaborative and Therapeutic Assessmementioning
confidence: 99%
See 1 more Smart Citation
“…Adult and adolescent clients are found to possess greater self--knowledge and an increased sense of self--efficacy (Finn & Thonsager, 1997), as well as stronger therapeutic alliance and engagement in later psychotherapy after the assessment has been completed (Ackerman, Hilsenroth, Baity, & Blagys, 2000). Positive outcomes--including higher treatment acceptability, significantly decreased child symptomatology, and enhanced family functioning are also reported upon finishing therapeutic assessment with children and their families (Tharinger, et al, 2009). In sum, the TA has been developed to make psychological assessment a positive and meaningful experience for clients and has been shown to be psychologically beneficial to clients.…”
Section: Chapter One: Introductionmentioning
confidence: 92%
“…Particularly, a study was conducted to study the efficacy of the TA--C with 14 children and their parents in a university clinic setting. It found that both children and their mother reported positive outcomes, including higher treatment acceptability, decreased child and parental symptomatology and better family functioning after participating in the TA (Tharinger, et al, 2009). …”
Section: Finn's Model Of Therapeutic Assessmentmentioning
confidence: 99%